2020
DOI: 10.1021/acssynbio.0c00338
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR-Cas13d for Gene Knockdown and Engineering of CHO Cells

Abstract: Chinese hamster ovary (CHO) cells are the predominant cell chassis for biopharmaceutical production. Engineering cellular pathways related to cell death, metabolism, and glycosylation in CHO cells is desired but challenging. Here, we present a novel approach that exploits CRISPR-Cas13d for gene silencing and CHO cell engineering. CRISPR-Cas13d is a burgeoning system that exploits Cas13d nuclease and guide RNA (gRNA) for RNA cleavage and gene knockdown. We first showed that CRISPR-Cas13d effectively knocked dow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 48 publications
0
11
1
Order By: Relevance
“…With stable integration of the CRISPRi system targeting two sites upstream of TSS of the Fut8 gene, we were able to downregulate its expression by an average of ∼ 50% in the pool of CHO cells (Figure 1B and E). This is in contrast with the previous report about S. pyogenes-derived dCas9-KRAB based CRISPRi system not being effective in Fut8 gene repression, [45] pointing to a difference in the effectiveness of different CRISPRi systems as well as the need for screening for the optimal sgRNA. The simultaneous targeting of multiple sgRNAs to the same gene (Figure 1) had a similar effect as individual transfections (Figure S1) and did not lead to more potent gene downregulation, as reported previously.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…With stable integration of the CRISPRi system targeting two sites upstream of TSS of the Fut8 gene, we were able to downregulate its expression by an average of ∼ 50% in the pool of CHO cells (Figure 1B and E). This is in contrast with the previous report about S. pyogenes-derived dCas9-KRAB based CRISPRi system not being effective in Fut8 gene repression, [45] pointing to a difference in the effectiveness of different CRISPRi systems as well as the need for screening for the optimal sgRNA. The simultaneous targeting of multiple sgRNAs to the same gene (Figure 1) had a similar effect as individual transfections (Figure S1) and did not lead to more potent gene downregulation, as reported previously.…”
Section: Discussioncontrasting
confidence: 99%
“…Even more pronounced effect was observed on the Fc domain, where fucosylation was decreased by up to 60% (Figure 3C). Although using IgG as a model protein, the authors of a recently published study reported that knockdown of Fut8 gene expression for ∼ 80% to 90% led to a decrease in fucosylation for only 30%, [ 45 ] reaffirming that type of therapeutic protein as well as other cell line characteristic can significantly contribute to fucosylation variability. [ 40 ] The model protein used in the study is Fc‐fusion protein consisting of two structurally and functionally distinct protein domains, with multiple N‐glycosylation sites on the target‐binding domain and one on the Fc‐domain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, knockdown of the FUT8 gene causes attenuation of IgG fucosylation with 90% efficiency. Thus, their study has shown the generation of stable engineered CHO cells using the CRISPR-Cas13d platform, which has the ability to attenuate lactate accumulation and glycosylation and also shown apoptosis resistance which resulted in an increase in cell titer, enhance recombinant protein and antibody production during fed-batch culture ( Shen et al, 2020 ). Similarly, He et al, used active RfxCas13d to target metabolic genes including Pten, Pcsk9, and lncLstr, in mouse hepatocytes.…”
Section: Various Applications Of Cas13d In Basic Research and Biomedi...mentioning
confidence: 99%
“…Studies on CasRx-mediated knockdown have been reported in bacteria, 25 plants, 26 and various cell types. 27 , 28 For example, Zhou et al. 13 alleviated neurological disease in mice by knocking down Ptbp1 using CasRx, and Jiang et al.…”
Section: Introductionmentioning
confidence: 99%